Mammary analog secretory carcinoma of salivary glands: a report of 2 cases with expression of basal/myoepithelial markers (calponin, CD10 and p63 protein) - Laco, Jan; Švajdler, Marián; Andrejs, Jan; Hrubala, Dušan; Hácová, Mária; Vaněček, Tomáš; Skálová, Alena; Ryška, Aleš (Pathology, research and practice, 2013)
Mammary analog secretory carcinoma (MASC) of salivary glands is a recently described neoplasm with favorable outcome. We describe 2 cases of MASC occurring in a 34-year-old female and a 58-year-old male, both presenting with a swelling of upper lip and right parotid gland, measuring 15 and 20mm, respectively. Without adjuvant treatment, both patients have been free of disease for 15 months and 12 months since the operation. Microscopically, both tumors were cystic and showed tubular and cystopapillary architecture. The tumor cells had round to oval nuclei and eosinophilic cytoplasm. Presence of eosinophilic material was evident within cystic spaces. Immunohistochemically, both tumors expressed cytokeratins (CK), CK7, CK8, CK18, epithelial membrane antigen, vimentin, S-100 protein, mammaglobin, and STAT5a (signal transducer and activator of transcription 5a). Interestingly, both tumors showed variable expression of basal/myoepithelial markers. In one case, we observed diffuse expression of calponin and focal expression of p63 whereas expression of CD10 was absent. In the second case, the staining of calponin was negative, but there was focal expression of both p63 and CD10. Both neoplasms harbored the ETV6-NTRK3 fusion transcript as proved by RT-PCR. Although previously reported only rarely, we conclude that MASC may show expression of basal/myoepithelial markers.
Keywords: Carcinoma; Calponins; Membrane Proteins; Humans; Parotid Neoplasms; lidé středního věku; calponiny; In Situ Hybridization, Fluorescence; Biomarkers, Tumor; fúzní onkogenní proteiny; Calcium-Binding Proteins; Female; dospělí; polymerázová řetězová reakce s reverzní transkripcí; mikrofilamentové proteiny; lidé; Reverse Transcriptase Polymerase Chain Reaction; Immunohistochemistry; imunohistochemie; Oncogene Proteins, Fusion; karcinom; nádorové biomarkery; Adult; Breast Neoplasms; ženské pohlaví; Neprilysin; Male; hybridizace in situ fluorescenční; Middle Aged; proteiny vázající vápník; neprilysin; nádory prsu; Microfilament Proteins; membránové proteiny; mužské pohlaví; nádory příušní žlázy